Response of Roselle (Hibiscus sabdariffa L.) varieties to fertilizer type and rates in two agro-ecologies of Southwest Nigeria - Omoniyi Isiaq, Lawal; Adetoyese, Oyedokun O.; Hazanat, Hamzat O.T.; Adebola, Osipitan A. (Annals of Tropical Research, 2023)
Roselle is an important traditional vegetable that is drought resistant and tolerant to wide range of soil conditions. It responds well to fertilizer application for optimum productivity. Field trials were conducted simultaneously in Abeokuta and Ibadan in 2014 to evaluate the effect of different types and rates of fertilizer on the performance of roselle. The trials had fourteen treatment combinations fitted into split plot design with three replicates. Seven fertilizer rates made up of three organic fertilizer (2.5, 5.0, and 7.5t ha-1) Alesinloye organic fertilizer (AOF) and three NPK 15-15-15 fertilizer rates (200, 300 and 400 kg ha-1); no fertilizer (control) was applied on white and red roselle varieties. Data on plant height, number of leaves and branches, shoot dry weight, number of calyx/plant, and weight of dry calyx were collected. Application of 7.5t ha-1 AOF gave significantly (p<0.05) higher number of leaves (126.0 and 115. 1) for white roselle as compared to red with (91.7 and 80.8) at the two locations. Also, the 7.5t ha-1 AOF produced significantly (p<0.05) higher dry calyx yield (425.6 and 386.7kg ha-1) for white roselle relative to red (329.0 and 291.6kg ha-1) in Abeokuta and Ibadan, respectively. The 7.5t ha-1 AOF did better than other fertilizer treatments in this trial, hence recommended for optimum performance of roselle in southwest Nigeria.